Estudo do mecanismo de eletrodeposição de cobalto sobre Pt em sulfato na presença de ácido bórico - Santos, Janaina Soares (Universidade Federal de São Carlos, 2007)
In this work, the cobalt deposition and dissolution processes were studied. The experiments were performed in sulphate solutions at pH values (ranging from 4.9 to 5.5) and in the presence of boric acid. The mechanism of Co electrodeposition was investigated using cyclic voltammetry and current time transients coupled with Electrochemical Quartz Crystal Microbalance (EQCM) technique. Effects of temperature, potential deposition and boric acid and Co2+ concentrations were studied. The boric acid was used as buffer to prevent any pH changes due to hydrogen evolution reaction (HER) during the electrochemical measurements. However, in some special cases, the results show that Co(OH)2 was formed simultaneously with metallic Co on the electrode surface at 48oC. On the other hand, when the bath temperature was 25oC, only metallic Co was detected. Considering the results above, some hypothesis were presented for explaining the ineffectiveness of boric acid. First, the kinetics of boric acid dissociation of was very slow, so does not provide a significant buffering during H2 evolution in high temperature, in which HER is intense. Another hypothesis refers to neutral H3BO3 molecules adsorption on the electrode surface which decreases the active surface for proton discharge. At 48oC, the desorption rate is higher than at 25oC, so the active surface for proton discharge will increase in high temperatures. As result, the pH value can be rise and consequently Co(OH)2 will formed. In these cases, the process efficiency dropped down. The analysis of factorial design shows that the temperature and the Co2+ concentration were the most important parameters for the mechanism change in the Co electrodeposition.
Keywords: Eletrodeposição; Cobalto; Microbalança de cristal de quartzo; Hidróxido de cobalto; CIENCIAS EXATAS E DA TERRA::QUIMICA